Pengembangan Aplikasi Informasi Pencarian Sekolah Berbasis Android di Kota Padang - Taufik Gusman; Yance Sonatha; Meri Azmi (Ikatan Ahli Informatika Indonesia (IAII), 2018)
Nowadays, there are some improvement of people's needs along with technology development especially android. People wanted to get information about something as quickly as possible by only using their phone's application. One of the example is information about school (profile, location,etc). In Padang city, there are so many schools that scattered throughout all the regions.This research try to build an application that can give any kind of information about school that user's wanted by only using their own phone. This application built in both side user and client. This application has been implemented by using a mobile phone with at least android operating system 4.0 version (ice cream sandwich) and it is successful in identifying the user's location and getting the information about school that they wanted. Keywords : android, information system, Padang, school